11.6k views
1 vote
Answer the question. To determine the answer.

Answer the question. To determine the answer.-example-1
User Jay Prall
by
4.4k points

1 Answer

6 votes

Answer:


m = (8)/(9)

Explanation:

Given:


((6)/(2), (2)/(3)) and
(2(1)/(2), -(2)/(3))

Required:

Slope

SOLUTION:

Formula for slope is given as
m = (y_2 - y_1)/(x_2 - x_1)

Let,


((6)/(2), (2)/(3)) = (x_1, y_1)


(2(1)/(2), -(2)/(3)) = (x_2, y_2)


m = (-(2)/(3) - (2)/(3))/((3)/(2) - (6)/(2))


m = ((-2 - 2)/(3))/((3 - 6)/(2))


m = ((-4)/(3))/((-3)/(2))


m = ((-4)/(3))/((2)/(-3))


m = (-4(2))/(3(-3))


m = (-8)/(-9)


m = (8)/(9)

User Dasf
by
5.3k points